Identifikasi Fungi Patogen Penyebab Penyakit Pada Tegakan Pohon Agathis labillardieri di Kampung Rimbajaya Kabupaten Biak Numfor, Papua - Siregar, Martha D.; Tanjung, Rosye H.R. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
This research aimed to determine the presence of disease, characteristics of pathogenic fungi and to identify pathogenic fungi that attack Agathis labillardieri tree stands. This research was conducted on the A. labillardieri plantations in Rimbajaya Village, East Biak District, Biak Numfor Regency and the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Cenderawasih University from November 2019 to January 2020. The research method began with a field survey, determining samples using purposive sampling, sampling, isolation of pathogenic fungi, purification of isolates, Koch's Postulates, and identification of pathogenic fungi. Based on the research results, it was known that stands of A. labillardieri trees were attacked by leaf rust, stem cancer and conk (fruit body) with isolates from the genus Curvularia and D1N on the leaves, the genus Rhizoctonia on stem cancer and B5M isolates from the conk (fruit body). Key words: A. labillardieri; fungi; plant disease; pathogen